Acceleration of vascularized bone tissue-engineered constructs in a large animal model combining intrinsic and extrinsic vascularization - Weigand, Annika; Beier, Justus; Heß, Andreas; Gerber, Thomas; Arkudas, Andreas; Horch, Raymund E.; Boos, Anja (Tissue Engineering: Parts A, B, and C, 2015)
During the last decades, a range of excellent and promising strategies in Bone Tissue Engineering have been developed. However, the remaining major problem is the lack of vascularization. In this study, extrinsic and intrinsic vascularization strategies were combined for acceleration of vascularization. For optimal biomechanical stability of the defect site and simplifying future transition into clinical application, a primary stable and approved nanostructured bone substitute in clinically relevant size was used. An arteriovenous (AV) loop was microsurgically created in sheep and implanted, together with the bone substitute, in either perforated titanium chambers (intrinsic/extrinsic) for different time intervals of up to 18 weeks or isolated Teflon(®) chambers (intrinsic) for 18 weeks. Over time, magnetic resonance imaging and micro-computed tomography (CT) analyses illustrate the dense vascularization arising from the AV loop. The bone substitute was completely interspersed with newly formed tissue after 12 weeks of intrinsic/extrinsic vascularization and after 18 weeks of intrinsic/extrinsic and intrinsic vascularization. Successful matrix change from an inorganic to an organic scaffold could be demonstrated in vascularized areas with scanning electron microscopy and energy dispersive X-ray spectroscopy. Using the intrinsic vascularization method only, the degradation of the scaffold and osteoclastic activity was significantly lower after 18 weeks, compared with 12 and 18 weeks in the combined intrinsic-extrinsic model. Immunohistochemical staining revealed an increase in bone tissue formation over time, without a difference between intrinsic/extrinsic and intrinsic vascularization after 18 weeks. This study presents the combination of extrinsic and intrinsic vascularization strategies for the generation of an axially vascularized bone substitute in clinically relevant size using a large animal model. The additional extrinsic vascularization promotes tissue ingrowth and remodeling processes of the bone substitute. Extrinsic vessels contribute to faster vascularization and finally anastomose with intrinsic vasculature, allowing microvascular transplantation of the bone substitute after a shorter prevascularization time than using the intrinsic method only. It can be reasonably assumed that the usage of perforated chambers can significantly reduce the time until transplantation of bone constructs. Finally, this study paves the way for further preclinical testing for proof of the concept as a basis for early clinical applicability.
EVALuna2:15582